2015
DOI: 10.1016/j.jhsa.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Cubital Tunnel Syndrome: Trends and the Influence of Patient and Surgeon Characteristics

Abstract: Purpose Cubital tunnel syndrome is the second most common compression neuropathy in the upper extremity. A variety of procedures are used for treatment of cubital tunnel syndrome. There is a lack of consensus regarding the most appropriate procedure owing to similar rates of operative success and strong proponents for each technique. Our aim was to examine trends in and determinants of the use of different procedures for treatment of cubital tunnel syndrome. Methods We performed a retrospective cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…The popularity of in situ decompression has increased in recent years as randomized controlled trials have not demonstrated the superiority of any single surgical procedure for cubital tunnel syndrome. 39 We believe our data indicating reduced surgical morbidity associated with open in situ decompression versus transposition offers another factor to consider when choosing a primary surgery for cubital tunnel syndrome. Although patient-reported health measures indicate similar outcomes after 8 weeks, earlier improvement or more rapid return to function may be highly valued by some patients.…”
Section: Discussionmentioning
confidence: 77%
“…The popularity of in situ decompression has increased in recent years as randomized controlled trials have not demonstrated the superiority of any single surgical procedure for cubital tunnel syndrome. 39 We believe our data indicating reduced surgical morbidity associated with open in situ decompression versus transposition offers another factor to consider when choosing a primary surgery for cubital tunnel syndrome. Although patient-reported health measures indicate similar outcomes after 8 weeks, earlier improvement or more rapid return to function may be highly valued by some patients.…”
Section: Discussionmentioning
confidence: 77%
“…14 Free to surgeons and American Association for Accreditation of Ambulatory Surgery Facilities-accredited surgery centers. 15 American Society for Plastic Surgeons fee, $125 application; $1274 annual. (Table 3).…”
Section: Attributes Of Large Administrative Databasesmentioning
confidence: 99%
“…Squiteri et al 14 found racial and insurancebased disparities in pediatric replantation rates using the KID database. Using the 2006 through 2012 Florida SASD, Adkinson et al 15 found that rates of in situ release for ulnar nerve decompression are rising, and rates of nerve transposition are decreasing. In addition, surgeons in the highest category of cubital tunnel surgery case volume were substantially more likely to perform in situ release.…”
Section: Healthcare Cost and Utilization Projectmentioning
confidence: 99%
“…Conservative treatment is firstly recommended to CuTS patients with mild symptoms, and if conservative treatment fails, operative treatment is indicated. 5 There are three main surgical procedures for CuTS patients, including in situ decompression, medial epicondylectomy, and intramuscular, submuscular, or subcutaneous anterior transposition of the ulnar nerve, but which one is the optimal procedure remains controversial. 6 8 Among these procedures, anterior transposition of the ulnar nerve is commonly used by many surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…In consideration of this situation, simple in situ decompression of the ulnar nerve, which seems to achieve similar postoperative results to transposition of the ulnar nerve, has gained popularity gradually. 5 , 9 …”
Section: Introductionmentioning
confidence: 99%